2011
DOI: 10.1007/s10336-011-0722-1
|View full text |Cite
|
Sign up to set email alerts
|

Nest size and breeding success in first and replacement clutches: an experimental study in Blue Tits Cyanistes caeruleus

Abstract: Bird nests function to protect parents, eggs or offspring against fluctuations in the environment. In Blue Tits (Cyanistes caeruleus) producing first or replacement clutches, we examined relationships between nest height (a measure of nest size) and several parameters of breeding performance that are often quantified in long-term avian field studies. We artificially increased the cost of reproduction in randomly selected females by removing the whole first clutch and nest material after about 5 days of incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 48 publications
4
80
1
1
Order By: Relevance
“…The contrasting findings of these two studies suggest that the availability of food influences nest building females in complex ways that vary over temporal and spatial scales and further studies in which blue tits or great tits are provided with supplementary food during the nest building period would be informative. Nevertheless, when the nests and eggs of experimental blue tit pairs were removed after 5 days of incubation so that they were forced to build their nests again, they built smaller nests and laid smaller replacement clutches (Lambrechts et al, 2012). Thus, there is evidence that nest building is an energetically expensive activity that is limited by the availability of food (Martin, 1987) in birds generally and also in blue tits, and probably therefore also in great tits, meaning that their nest building behaviors are extended phenotypic signals of the females' quality and may play a role in sexual selection.…”
Section: Sexual Selectionmentioning
confidence: 99%
“…The contrasting findings of these two studies suggest that the availability of food influences nest building females in complex ways that vary over temporal and spatial scales and further studies in which blue tits or great tits are provided with supplementary food during the nest building period would be informative. Nevertheless, when the nests and eggs of experimental blue tit pairs were removed after 5 days of incubation so that they were forced to build their nests again, they built smaller nests and laid smaller replacement clutches (Lambrechts et al, 2012). Thus, there is evidence that nest building is an energetically expensive activity that is limited by the availability of food (Martin, 1987) in birds generally and also in blue tits, and probably therefore also in great tits, meaning that their nest building behaviors are extended phenotypic signals of the females' quality and may play a role in sexual selection.…”
Section: Sexual Selectionmentioning
confidence: 99%
“…After removing the front door of the box (cf. Lambrechts et al 2012Lambrechts et al , 2016, we quantified nest building by measuring the vertical height of the external nest wall at 60.5 cm (measured from the bottom of the nest box to the top of the nest rim on the frontal part of the nest), also called ''nest depth'' (Hansell 2000), ''nest height'' (Lambrechts et al 2012), or ''nest thickness '' (Hurtrez-Boussès et al 1999). Thus, nest volume as a proxy of nest size was estimated by multiplying nest height with the inner surface of the standardized box floor (cf.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from testing experimentally the roles of photoperiod and temperature, we also controlled for the influence of 2 other potential determinants of nest size, namely clutch size and laying date. Several studies have indeed explored and reported relationships between nest size, laying date, and/or clutch size (e.g., Moreno et al 2008, Lambrechts et al 2012, 2017, Møller et al 2014. For example, early breeders or birds breeding in colder conditions could have the option to build larger, more insulated, nests and/or to lay larger clutches, thereby decreasing heat loss.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations